DESAIN TERAS ALTERNATIF UNTUK REAKTOR RISET INOVATIF (RRI) DARI ASPEK NEUTRONIK - Kuntoro, Iman; Sembiring, Tagor Malem (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Based on its User Requirement Document and main function, RRI shall be able to provide a maximum thermal neutron flux of 1×1015 neutron cm-2s-1. The reason is that the RRI reactor can serve targets requiring a high neutron flux. From the previous results it was obtained that RRI design using fuel of RSG-GAS type was not possible to produce that high neutron flux. One among other reasons is that the geometry dimension is the large, as the neutron flux is inversely proportional to core volume. The objective of the study is to find an alternative core for RRI which meets the high neutron flux requirement. It was chosen an alternative fuel element one like used in JMTR (Japan Material Testing Reactor) that has smaller dimension compared to that of the RSG-GAS reactor. Besides that, active core’s height was also varied for 70 cm and 75 cm. Design was carried out by means of analytic codes WIMS-D5B, Batan-FUEL and Batan-3DIFF. Alternative core applied compact core configuration concept of 5×5 with 4 follower control elements. The calculations resulted 3 (three) alternative cores fulfill the requirement, including core using RSG-GAS fuel type but of 70 cm height instead of 60 cm. Through analyzing from over all aspects of core safety and efficiency as well as effectively, core using JMTR fuel type with height of 70 cm represent the best alternative core.